CD9 Controls Integrin α5β1-Mediated Cell Adhesion by Modulating Its Association With the Metalloproteinase ADAM17 - Machado-Pineda, Yesenia; Cardeñes, Beatriz; Reyes, Raquel; López-Martín, Soraya; Toribio, Víctor; Sánchez-Organero, Paula; Suarez, Henar; Grötzinger, Joachim; Lorenzen, Inken; Yáñez-Mó, María; Cabañas, Carlos (Frontiers in Immunology, 2018)
Integrin α5β1 is a crucial adhesion molecule that mediates the adherence of many cell types to the extracellular matrix through recognition of its classic ligand fibronectin as well as to other cells through binding to an alternative counter-receptor, the metalloproteinase ADAM17/TACE. Interactions between integrin α5β1 and ADAM17 may take place both in trans (between molecules expressed on different cells) or in cis (between molecules expressed on the same cell) configurations. It has been recently reported that the cis association between α5β1 and ADAM17 keeps both molecules inactive, whereas their dissociation results in activation of their adhesive and metalloproteinase activities. Here we show that the tetraspanin CD9 negatively regulates integrin α5β1-mediated cell adhesion by enhancing the cis interaction of this integrin with ADAM17 on the cell surface. Additionally we show that, similarly to CD9, the monoclonal antibody 2A10 directed to the disintegrin domain of ADAM17 specifically inhibits integrin α5β1-mediated cell adhesion to its ligands fibronectin and ADAM17.